The Blazing World - Cavendish, Margaret (Dover Publications, Incorporated, 2019)
Written by a 17th-century duchess, this remarkable utopian fantasy centers on a heroine who is transported to another world, where she rules as empress and outlaws war, religious conflict, and gender discrimination. Intro – Title Page – Copyright Page – Note – Contents – To the Reader – The Description of a New World, Called the Blazing World – The Second Part of the Description of the New Blazing World – The Epilogue: To the Reader.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books